Rancang Bangun Rangka Sun Tracking Pada Panel Surya Dinamik - Mafiqi, Arif; G, Yogie Rinaldy; Prayitno, Adhy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study aims to design a Sun Tracking frame in dynamic solar panels. The methodology of this research has 4 main steps: (1) Literature Study, (2) Design Concepts, (3) Concept Selection, (4) Frame Making. in this study a Sun Tracking machine designed for solar cells was designed to follow the movement of the sun. The design stages consist of needs analysis, preparation of product technical specifications, design of product concepts to produce alternative product concepts which are then selected concepts to be made. From the form of the concept that will be made, static analysis is carried out on the mechanical components of the Sun Tracking engine. Static analysis is done by means of manual calculation and elemental analysis. Based on the results of the static analysis, the results of the stresses were 8.381 MPa on stem 1, 8.769 MPa on rod 2, 0.5378 MPa on rod 3 and 0.6448 MPa on rod 4. Deformation that occurred was 0.02783 mm at stem 1, 0.03107 mm on stem 2, 0.0003228 mm on stem 3 and 0.0002346 mm on stem 4. Keywords: Sun Tracking, solar cell